TEACHERS' DIGITAL COMPETENCE IN DESIGNING INTERACTIVE LANGUAGE LEARNING MATERIALS FOR STUDENT-CENTERED EFL CLASSROOM PRACTICES - Dewi Afriany Susanti; Tina Sheba Cornelia Sitompul; Nurul Fatehah Binti Norhazaruddin (Sensei International Journal of Education and Linguistic, 2025)
Nowadays there are many digital applications that can be used to make interactive learning materials, but not all teachers are able to use them well. Some teachers can operate the application but the material that they make is not interactive. This study discusses teachers' digital competence in designing interactive language learning materials. The study used a mixed-method design. The data were collected through a questionnaire, the materials made by the teachers, and interviews. The result shows that the digital competence of the teachers is in the moderate category and there are still some obstacles such as limited time and limited training. Therefore, the school should give more training to the teachers.